Electrodeposition of Ni–MoS2 as effective hydrogen evolution reaction catalysts in alkaline media - Purshotham P. Katti; B.M. Praveen; Bharath K. Devendra; S Varadaraj; J.R. Naveen Kumar (Hybrid Advances)
Highly active, long-lasting, and economically feasible nonprecious metal-based electrocatalysts are urgently required for the slow hydrogen evolution reaction (HER) in alkaline conditions. Direct current (DC) electrodeposition was used to develop the highly active Ni–MoS2 composite coatings for efficient hydrogen generation. Scanning electron microscopy (SEM), Energy Dispersive X Ray Spectroscopy (EDS), X-ray diffraction (XRD), and linear sweep voltammetry (LSV) were used to evaluate the coatings. Ni–MoS2 composite coatings behaved almost identically to pure platinum metal. The Ni–MoS2 coating produced 1.0 g/l demonstrated a low overpotential for HER. The HER process's analyzed from Volmer-Tafel mechanistic route has an extremely low slope of 56.5 mV/dec. All the coated samples were subjected to chronopotentiometry (CP). This catalyst's high HER performance shows that it has significant potential for practical applications.